2017
DOI: 10.1007/s10750-017-3295-z
|View full text |Cite
|
Sign up to set email alerts
|

Single colony genetic analysis of epilithic stream algae of the genus Chamaesiphon spp.

Abstract: In order to understand Chamaesiphon spp. evolution and ecological diversification, we investigated the phylogenetic differentiation of three morphospecies from field samples by means of single colony genetics. Individual colonies of three different morphospecies (C. starmachii, C. polonicus, C. geitleri,) were isolated from lotic gravel streams and their 16S rDNA nucleotide variability was analyzed. For a number of individual colonies, microscopical and ultrastructural analysis was also performed. A phylogenet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 36 publications
3
21
0
Order By: Relevance
“…The 16S rRNA gene sequencing of the previously morphologically defined genus of planktic cyanobacteria Sphaerocavum have brought evidence for its identity with Microcystis, while detailed analysis of the rRNA ITS data suggested that it was a separate species within this genus. Another study focused on a single genus, Chamaesiphon, where a reproducible protocol for single-colony sequencing of epilithic cyanobacteria in streams was developed (Kurmayer et al, 2017). The SSU rRNA data obtained in that study did not allow any firm conclusions regarding the present species as the morphology and ultrastructure data were not congruent with the reconstructed phylogeny.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 16S rRNA gene sequencing of the previously morphologically defined genus of planktic cyanobacteria Sphaerocavum have brought evidence for its identity with Microcystis, while detailed analysis of the rRNA ITS data suggested that it was a separate species within this genus. Another study focused on a single genus, Chamaesiphon, where a reproducible protocol for single-colony sequencing of epilithic cyanobacteria in streams was developed (Kurmayer et al, 2017). The SSU rRNA data obtained in that study did not allow any firm conclusions regarding the present species as the morphology and ultrastructure data were not congruent with the reconstructed phylogeny.…”
Section: Resultsmentioning
confidence: 99%
“…The thematic clusters of contributions in this special section (Supplementary Table 1) comprised the following: (i) problems and developments of the polyphasic evaluation of cyanobacterial biodiversity on the generic and suprageneric levels (Komárek, 2017;Mareš, 2017), and on the infrageneric level (Kurmayer et al, 2017;Rigonato et al, 2017), based on phylogenetic taxonomy; (ii) implementation of the results of modern taxonomic surveys into practical applications such as floristic and environmental research (Davydov & Patova, 2017;Komárek, 2017); (iii) molecular and morphological diversity and adaptation of taxa and/or OTUs to special environments and niches assessed by next-generation sequencing Ruber et al, 2017;Vogt et al, 2017); and (iv) occurrence of specific morphospecies and communities linked to and regulated by specific environmental characteristics in biocalcified lowland streams (Pentecost, 2017), alpine streams (Kurmayer et al, 2017), stratified freshwater lakes (Ruber et al, 2017), and marine tidal flats . The main merits and the taxonomic and biogeographic scope of the individual contributions are summarized in Online Supplemental Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyphasic approaches integrating morphological, ecological, adaptive‐biology, molecular‐phylogeny and bioorganic‐chemistry data are vital not only when dealing with morphology‐poor strains, but also when the reconciliation of morphological and genetic data is difficult or impossible without additional evidence (Kurmayer et al. ).…”
mentioning
confidence: 99%
“…It is now accepted that light microscopy has limitations for accurate species recognition and delimitation, especially of morphologically simple coccoid algae, which are common in soils (Fu c ıkov a et al , Leliaert et al 2014, Leliaert and De Clerck 2017. Polyphasic approaches integrating morphological, ecological, adaptive-biology, molecular-phylogeny and bioorganic-chemistry data are vital not only when dealing with morphology-poor strains, but also when the reconciliation of morphological and genetic data is difficult or impossible without additional evidence (Kurmayer et al 2017).…”
mentioning
confidence: 99%